Phenotypic and Molecular Study of Moraxella catarrhalis and their Virulence Genes in Patientswith Respiratory Infections - Sattar Gaber Ajeel; Zena M. Qaraghoi (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study aimed to investigate of Moraxella catarrhalis in respiratory tract and Virulence Genes. Sixteen(60) swabs were collected from patients suffering from respiratory tract, and were submitted to Baghdadmedical city. The result ahowed three (5%) from 60(100%)patients suffering from respiratory tract positivewith Moraxella catarrhalis with the usp A1, cop B and omp CD. From this study concluded Moraxellacatarrhalis is pathogenic to man if it is isolated from respiratory tract , as well as usp A1 , cop B and ompCD are common in all Moraxella catarrhalis isolates. So, future molecular studies were needed to compareMoraxella isolated as normal flora or pathogen , antibiogram profile should be investigated at molecularlevel and investigation on some virulence factors other than those studied in this thesis